ANALISIS STRATEGI PENGEMBANGAN AGROINDUSTRI IKAN AIR TAWAR UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT (Studi Pada Nelayan Bendungan Batu Bulan Desa Maman) - Roos Nana Sucihati; K Kamaruddin; Ayu Sukma Utami (Jurnal Ekonomi & Bisnis, 2021)
This study aims to know the impact of internal and external factors of the BatuBulan Dam Freshwater Fish Agroindustry in Increasing the Income of the Maman Village Fisherman Community and to know the strategy of developing BatuBulan Dam Freshwater Fish Agroindustry.The type of this study was descriptive qualitative. The number of informants in this study were 65 which consisted of 58 of key informants and 5 of main informants. The data used in this study was primary. Method used to collect data was through interviews. The data analysis tool used was SWOT analysis. The results of study showed that based on the results of the SWOT analysis that strategy for the development of the Freshwater Fish Agroindustry of Maman Village could be done based on consideration of strengths, weaknesses, opportunities and threats showed that if it was managed properly and maximally, the income and economy of the fishermen community in Maman Village would increase. The strength factor in this study was the large amount of fish catch and varies, good response from the community and increased community income after the existence of agro-industry. While the weaknesses were the lack of facilities and infrastructure, there were not industrial factory yet and the lack of processing equipment of cath.